1014 Higher Specialist Training in Ireland. Learning from the Graduates 2005–2011. (October 2012) - Freyne, BJ; Nicholson, AJ; O'Neill, MB
Abstract : Background and Aims: The Higher Specialist Training (HST) program in General Paediatrics was initiated in 1999. The first graduates to complete the full program received their CSCST in 2005. There are 15 graduates per year. This study evaluated whether graduates believed core competencies of the HST curriculum were achieved and assessed their perceptions of its strengths and weaknesses. Methods: The lack of an accurate database resulted in a convenience sample being utilized. Demographic data obtained included year of program entry and current position. The survey utilized a Likert scoring system (cuing at 1, not at all, cuing at 6, definitely) to evaluate the training process relating to clinical skills, research abilities, health economics. Qualitative questions allowed for personal reflections on the training process both positive and negative. Responses were analyzed for themes. Results: Data were analyzed from a convenience sample of 25 responses (1/3 of all trainees). The M:F ratio was 3:1. Twenty three graduates (92%) completed overseas fellowships. Mean Likert scores were clinical competency (4.8), basic science knowledge (4.9), evidence based medicine application (3.7), ability to work as academic supervisor (3.3), research skills (2.9), health economics (2.3) and health policy (2.3). Negative themes from qualitative analysis included the adverse impact of excessive service provision on training and the lack of structured career advancement. Most felt clinically competent compared to international colleagues. Conclusion: Clinical competency is achieved through the HST program. Specific training is required for health management, policy and research aspects of training.